Application of prescribing recommendations in older people with reduced kidney function: a cross-sectional study in general practice - Wood, Su; Petty, Duncan; Glidewell, Liz; Raynor, Dk Theo (British journal of general practice, 2018)
Kidney function reduces with age, increasing the risk of harm from increased blood levels of many medicines. Although estimated glomerular filtration rate (eGFR) is reported for prescribing decisions in those aged ≥65 years, creatinine clearance (Cockcroft-Gault) gives a more accurate estimate of kidney function. To explore the extent of prescribing outside recommendations for people aged ≥65 years with reduced kidney function in primary care and to assess the impact of using eGFR instead of creatinine clearance to calculate kidney function. A cross-sectional survey of anonymised prescribing data in people aged ≥65 years from all 80 general practices (70 900 patients) in a north of England former primary care trust. The prevalence of prescribing outside recommendations was analysed for eight exemplar drugs. Data were collected for age, sex, actual weight, serum creatinine, and eGFR. Kidney function as creatinine clearance (Cockcroft-Gault) was calculated using actual body weight and estimated ideal body weight. Kidney function was too low for recommended prescribing in 4-40% of people aged ≥65 years, and in 24-80% of people aged ≥85 years despite more than 90% of patients having recent recorded kidney function results. Using eGFR overestimated kidney function for 3-28% of those aged ≥65 years, and for 13-58% of those aged ≥85 years. Increased age predicted higher odds of having a kidney function estimate too low for recommended prescribing of the study drugs. Prescribing recommendations when kidney function is reduced are not applied for many people aged ≥65 years in primary care. Using eGFR considerably overestimates kidney function for prescribing and, therefore, creatinine clearance (Cockcroft-Gault) should be assessed when prescribing for these people. Interventions are needed to aid prescribers when kidney function is reduced.